Sustainable Treatment and Reuse of Municipal Wastewater For decision makers and practising engineers - Libhaber, Menahem (IWA Publishing, 2012)
In many countries, especially in developing countries, many people lack access to water and sanitation services and this inadequate service is the main cause of diseases in these countries. Application of appropriate wastewater treatment technologies, which are effective, low cost, simple to operate, proven technologies, is a key component in any strategy aimed at increasing the coverage of wastewater treatment. Sustainable Treatment and Reuse of Municipal Wastewater presents the concepts of appropriate technology for wastewater treatment and the issues of strategy and policy for increasing wastewater treatment coverage. The book focuses on the resolution of wastewater treatment and disposal problems in developing countries, however the concepts presented are valid and applicable anywhere and plants based on combined unit processes of appropriate technology can also be used in developed countries and provide to them the benefits described.